Answer:
=81/7
Explanation:
Simplifying
6X + 18 + 8x + -2 = 180
Reorder the terms:
18 + -2 + 6X + 8x = 180
Combine like terms: 18 + -2 = 16
16 + 6X + 8x = 180
Solving
16 + 6X + 8x = 180
Solving for variable 'X'.
Move all terms containing X to the left, all other terms to the right.
Add '-16' to each side of the equation.
16 + 6X + -16 + 8x = 180 + -16
Reorder the terms:
16 + -16 + 6X + 8x = 180 + -16
Combine like terms: 16 + -16 = 0
0 + 6X + 8x = 180 + -16
6X + 8x = 180 + -16
Combine like terms: 180 + -16 = 164
6X + 8x = 164
Add '-8x' to each side of the equation.
6X + 8x + -8x = 164 + -8x
Combine like terms: 8x + -8x = 0
6X + 0 = 164 + -8x
6X = 164 + -8x
Divide each side by '6'.
X = 27.33333333 + -1.333333333x
Simplifying
X = 27.33333333 + -1.333333333x